Analisis Sifat Fisiko Kimia Nasi dari Beras Nutrizink dan Ciherang Gorontalo - Akilie, Muhammad Sudirman; Fitriani, A Nur; Abudi, Ikran (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2023)
The aim of this research was to analize the physics-chemical such as water, zinc, whiteness index level and the organoleptic consist of the taste, colour, oudor, texture of nutrizink and ciherang rice from Gorontalo. The design of this research used factorial completely randomized design with two factors, which the first and the second factors were variety of rice and ratio water rice. The four treatments were nutrizink rice 200gram: water 200 ml, nutrizink rice 200gram: water 400 ml, ciherang rice 200gram: water 200 ml, ciherang rice 200gram: water 400 ml with three replications. The results showed that the factors of various rice and ratio water rice did not affect significantly on water level but it affected significantly to zinc level. The factor of ratio rice and water had whiteness index level significantly. There were no interaction factors between various of rice and ratio water rice on water, zinc and whiteness index level of nutrizink and ciherang rice from Gorontalo. The treatment of nutrizink rice, ratio of water and rice 1:2 = rice 200gram water 400 ml was the best base on the panelists acceptance of the taste, colour, oudor and texture of nutrizink and ciherang rice.